WAYS TO IMPROVE THE METHODS OF CALCULATING TERRITORIAL INDICATORS OF THE NATIONAL ACCOUNTING SYSTEM - Qurbandurdievich, Mambetjanov Qahramon; Artikovich, Abdullayev Suyun (The journal of contemporary issues in business and government, 2021)
This article presents the essence of the calculation of GRP and its features, the main problems of its application in the statistical system of Uzbekistan and ways to eliminate these problems, as well as scientific proposals and practical recommendations for improving the computation of GRP.